Possibility of using the infrapatellar (Hoffa’s) fat pad as a source of autologous stem cells - A. V. Korel (Сибирский научный медицинский журнал, 2020)
Stem cells are the basis for the creation of tissue-engineered structures in regenerative medicine. The most well-studied sources of stem cells are the embryo and bone marrow. The use of embryonic cells is associated with ethical problems, and the collection of bone marrow is accompanied by invasive procedures. Using adipose tissue as a source of stem cells avoids these problems. But the collection of adipose tissue requires additional interventions, which does not exclude the occurrence of cosmetic defects. Aim of the study was to investigate the possibility of using mesenchymal stem cells (MSCs) isolated from the infrapatellar (Hoffa’s) fat pad.Material and methods. As a source of MSCs, tissue samples of Hoffa’s fat pad removed during the operation were used (8 cases), as a control - MSCs isolated from human adipose tissue (6 cases). MSCs were isolated using an enzymatic method. At the 3rd passage, phenotyping with specific antibodies against CD34, CD45, CD73, CD90, CD105 was performed by flow cytometry. Differentiation in the chondro- and osteogenic direction was carried out at the 3rd passage with the appropriate differentiation media. Chondrogenic differentiation was confirmed by staining with alcian blue, osteogenic - staining according to von Kossa.Results and discussion. Statistically significant decrease in CD105 expression, increase in CD73, CD34 expression and lack of adequate differentiation under standard conditions of differentiation media by MSCs isolated from the Hoffa’s fat pad compared to control was found. The data obtained indicate a discrepancy between the cells isolated from the Hoffa’s fat pad and the requirements for MSCs.Conclusion. The infrapatellar (Hoffa’s) fat pad_cannot be used as a source of standardized MSCs.